Análisis Antropogénico Y Del Cambio Climático Que Impactan Los Paramos, Complejo Cruz Verde (2023)
Paramos are ecosystems located in tropical and subtropical regions known for their wide diversity of species and provide a variety of diverse ecological services to local communities and nearby cities. However, these complexes are leading to important threats from global stressors, global such as climate change and impacts on earth.